Properties of quarter-wavelength coaxial cavity for triode-type thermionic RF gun. (4th August 2017) - Torgasin, Konstantin; Mishima, Kenta; Zen, Heishun; Yoshida, Kohei; Negm, Hani; Omer, Muhamed; Kii, Toshiteru; Nagasaki, Kazunobu; Masuda, Kai; Ohgaki, Hideaki
Abstract: A quarter-wavelength coaxial cavity with a longitudinal radio-frequency power supply was fabricated and tested. The cavity was designed as a pre-buncher for a thermionic triode-type radio-frequency gun of a mid-infrared free electron laser facility. The triode structure was formed to ensure the reduction of the back-bombarding effect, which usually appears in thermionic radio-frequency guns. The coaxial cavity was tested using a tungsten dispenser cathode. From the results of the cold test, a cavity voltage of about 25 kV can be attained, which corresponds to designed characteristics. In contrast, the hot test showed a sudden drop in voltage, resulting in an unstable operation. The small dimensions of the cavity caused some low-field effects, which led to multipactoring. In this paper, we report the tested characteristics of the pre-bunching cavity.